2014
DOI: 10.3109/01443615.2014.991294
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for adverse clinical outcomes in patients with tubo-ovarian abscess

Abstract: This study assessed the risk factors for poor clinical outcomes in patients with tubo-ovarian abscess (TOA). Patients managed with medical therapy and discharged within 7 days without complications constituted the favourable prognosis group (n = 22), whereas those who were managed surgically or discharged after 7 days of antibiotic therapy constituted the poor prognosis group (n = 87). Variables including age, gravidity, number of dilation and curettage procedures, caesarean delivery, smoking status, serum C-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 23 publications
5
28
2
1
Order By: Relevance
“…In this study, they found the cut-off value for CRP and ESR levels as 6.7 mg/L and 50 mm/h, respectively (13). Unlike these studies, a significant difference was not observed in CRP levels and WBC count between the favorable or poor prognosis group in the study by Topçu et al (19). In our study, we found that there was no significant difference in CRP and ESR counts between the groups.…”
Section: Discussioncontrasting
confidence: 55%
“…In this study, they found the cut-off value for CRP and ESR levels as 6.7 mg/L and 50 mm/h, respectively (13). Unlike these studies, a significant difference was not observed in CRP levels and WBC count between the favorable or poor prognosis group in the study by Topçu et al (19). In our study, we found that there was no significant difference in CRP and ESR counts between the groups.…”
Section: Discussioncontrasting
confidence: 55%
“…The highest reported body temperature in patients with TOA was 37.6 °C ±0.6 °C in a study by Karakulak et al, and 37.24 °C ±0.788 °C in a study by Topçu et al 6,14 In the present study, the average body temperature in patients with TOA was 37.4°C ±0.77 °C, which was similar to that reported in the previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies reported leukocyte counts and CRP levels of 11.500-16.000/mm 3 and 7.6-14 mg/dL, respectively, in patients undergoing medical treatment, and 14000-16700/mm 3 and 16.1-53.8 mg/dL, respectively, in patients undergoing surgical treatment, indicating that leukocyte counts and CRP levels of patients undergoing surgical treatment were higher than those of patients undergoing medical treatment. 7,12,[14][15][16] In the present study, the mean leukocyte count and CRP level of patients undergoing medical treatment were 11.850/mm 3 and 11.1 mg/dL, respectively, while those of patients undergoing surgical treatment were 13.780/mm 3 and 14.1 mg/dL, respectively, and those of patients undergoing USG-guided drainage were 14.870/mm 3 and 16.2 mg/dL, respectively. These findings indicated that leucocyte counts and CRP levels of patients undergoing surgical treatment were higher than those of patients undergoing medical treatment, which was consistent with that reported in previ- ous studies.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations